MENINGKATKAN KEMAMPUAN OPERASI PENJUMLAHAN BILANGAN PECAHAN MELALUI METODE DEMONSTRASI - Eros Rosmawati (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
The background of the implementation of this classroom action research is the failure of students to achieve the KKM that has been determined in the addition of fractions in Mathematics learning. The purpose of this study was to improve students' ability in the addition of fractions in Mathematics learning in class VI SD Negeri Tanjungsari. This research was conducted in two cycles. in Class VI Tanjungsari State Elementary School, UPTD PAUD, PNFI, Kindergarten and Elementary School in Blanakan District, Subang Regency, with 24 students. The research method used is a descriptive method with a quantitative research approach. Research data collection was carried out through documentation studies of student learning outcomes from each cycle. The results showed an increase in the average value of student learning outcomes in the addition of fractions. This can be seen from the initial conditions before the action, the average value of student learning outcomes of 56.25%, after the first cycle of action an increase in the average value of student learning outcomes became 62.91%. Likewise, after the second cycle of action there was an increase in the average value of student learning outcomes to 73.75%.